You're Just My Type: Mate Choice and Behavioral Types. (September 2020) - Munson, Amelia A.; Jones, Cameron; Schraft, Hannes; Sih, Andrew
Abstract : Consistent individual differences in behavior [i.e., behavioral types (BTs)], are common across the animal kingdom. Consistency can make behavior an adaptive trait for mate choice decisions. Here, we present a conceptual framework to explain how and why females might evaluate a male's BT before mating. Because BTs are consistent across time or context, a male's BT can be a reliable indicator of his potential to provide direct benefits. Heritable BTs can enable informed mate choice via indirect benefits. Many key issues regarding patterns of mate choice, including sensory biases, context dependence, and assortative mating apply to BT-dependent mate choice. Understanding the relationship between BTs and mate choice may offer insights into patterns of variation and consistency common in behavioral traits. Highlights: Acknowledging the existence of consistent differences among individuals in behavior [i.e., behavioral types (BTs)] yields new insights on patterns of mate choice. Because BTs are both consistent over time and context, and are heritable, mate choice based on the partner's behavioral type can be adaptive. Choosing an individual's BT can affect its adaptive mate choice. Due to complex interactions between the sexes, their BTs, and environmental context, BT-dependent mate choice may help to explain the maintenance of variation between individuals in behavioral type. In addition, the social context and benefit of honest signaling that is a part of mate choice may contribute to why we see consistency within an individual in BT.